2006
DOI: 10.1007/s10482-006-9103-9
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of hexamethylenetetramine (urotropine) by bacteria and yeasts

Abstract: A slow growing bacterial population able to utilize hexamethylelenetetramine (urotropine) as sole source of carbon, nitrogen and energy was isolated from soil. From this crude enrichment culture two bacteria were isolated and identified as Brevundimonas diminuta and a Phyllobacterium sp. by sequencing of 16S ribosomal DNA. These bacteria also grew on urotropine but at a lower rate than the enrichment culture. Addition of glucose to the latter resulted in growth of some yeasts that overgrew the bacteria. Assimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The effect of increasing hexamine application rate on yeast numbers and ethanol content was different in the two experiments. In unwilted silage, S. cerevisiae numbers increased curvilinearly while ethanol content increased linearly with increasing hexamine rate, supporting the finding that hexamine may in some situations increase yeast fermentation. In wilted silage, increasing the hexamine rate decreased S. cerevisiae copy numbers while ethanol concentrations did not change, despite high residual WSC contents in the silages.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The effect of increasing hexamine application rate on yeast numbers and ethanol content was different in the two experiments. In unwilted silage, S. cerevisiae numbers increased curvilinearly while ethanol content increased linearly with increasing hexamine rate, supporting the finding that hexamine may in some situations increase yeast fermentation. In wilted silage, increasing the hexamine rate decreased S. cerevisiae copy numbers while ethanol concentrations did not change, despite high residual WSC contents in the silages.…”
Section: Discussionsupporting
confidence: 75%
“…Formaldehyde impairs lactic acid bacteria growth and increases pH . On the other hand, certain indigenous soil bacteria and yeasts use hexamine as a sole source of carbon, nitrogen, and energy . Based on that, increasing levels of hexamine in silage might simultaneously increase yeast fermentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The steam stripper separates the ammonia from the solution. Hexamine has a very stable structure which made the molecule recalcitrant to oxidation via methylotrophic pathway reactions so that very few microorganisms in soil can break it to utilize as sole source of carbon, nitrogen and energy (Middelhoven and van Doesburg 2007).…”
Section: Introductionmentioning
confidence: 99%
“…and M. bullata, are known to have the ability to biodegrade various xenobiotic aromatic compounds as sole carbon and energy sources. For example, B. diminuta has been identified as a PAH biodegrader in creosote-contaminated soils (Viñas et al, 2005) and has been shown to utilize hexamethylenetetramine (urotropine) and trifluralin (alpha, alpha, alphatrifluoro-2,6-dinitro-N,N-dipropyl-p-toluidine) as sole carbon source, sole nitrogen source and sole energy source (Bellinaso et al, 2003;Middelhoven and van Doesburg, 2007). Caulobacter spp.…”
Section: Factors Affecting Nap Biodegradation In the Presence Of Surfmentioning
confidence: 99%